Emancipatory Poetry: The Žemaitė Square Readings as Feminist Artivism - Šakelaitė, Ieva (Colloquia, 2024)
Although contemporary Lithuanian poets and readers often claim to be apolitical, politically charged poetry or literary behavior are not always apparent and can take various forms. The article examines the annual women’s poetry readings in the Žemaitė Square during the Poetry Spring Festival as a political event. Based on Pierre Bourdieu’s literary field theory, the event can be interpreted as a collective response of feminist artivism to the established power structures. The readings provide a space for the exchange of social, symbolic, and cultural capital among the poetesses, enabling them to gain visibility and prominence within the literary field. Furthermore, the political significance of these readings emerges through the experience of emancipatory art, as defined by Jacques Rancière. The ‘distribution of the sensible’ not only establishes poetesses as political subjects but also fosters a sense of potential equality among all agents in the field. The collective experience of art engenders an aesthetic community capable of challenging prevailing power structures and envisioning possibilities that extend beyond societal norms.
Keywords: artivism; artistic activism; feminism; sociology of literature; activist poetry; political poetry